Expression of Cartilage Oligomeric Matrix Protein in colorectal cancer is an adverse prognostic factor and correlates negatively with infiltrating immune cells and PD-L1 expression - Blom, Anna M.; Gialeli, Chrysostomi; Hagerling, Catharina; Berntsson, Jonna; Jirström, Karin; Papadakos, Konstantinos S. (Frontiers in Immunology, 2023)
Introduction Cartilage Oligomeric Matrix Protein (COMP) is an oncogenic protein that has been associated with a decrease in infiltrating T-cells in periampullary adenocarcinoma. This study aimed to investigate whether this is also the case for colorectal cancer (CRC) and to evaluate the relationship between COMP expression and clinopathological features. Methods Immunohistochemistry was used to determine the expression levels of COMP in tumor cells and stroma in primary tumors from a cohort of 537 CRC patients. The expression of immune cell markers, including CD3+, CD8+, FoxP3+, CD68+, CD56+, CD163+, and PD-L1, was evaluated previously. Tumor fibrosis was assessed by Sirius Red staining and evaluation of collagen fiber organization. Results COMP expression correlated positively with TNM-stage and grade of differentiation. Patients with CRC expressing high levels of COMP had significantly shorter OS than those with low COMP expression (p<0.0001), and fewer infiltrating T-cells were detected in tumors with high COMP expression. Additionally, a negative correlation was identified between the expression of COMP and PD-L1 on both tumor cells and immune cells. Cox regression analysis showed that tumors expressing high levels of COMP had significantly shorter OS, independent of all evaluated immune cell markers. Tumor fibrosis was correlated with high expression of COMP in the stroma (p<0.0001), and tumors with high levels of COMP expression and denser fibrosis displayed more sparse immune cell infiltration. Discussion The results suggest that COMP expression in CRC may exert an immune regulatory effect by increasing dense fibrosis and decreasing immune cell infiltration. These findings support the notion that COMP is an important factor in the development and progression of CRC.